Stigma perceived by mothers of children with congenital Zika virus syndrome - Deisyane Vitoria Alves; Paulo Roberto Lima Falcão do Vale; Sheila Santa Barbara Cerqueira; Cleuma Sueli Santos Suto; Aisiane Cedraz Morais; Evanilda Souza de Santana Carvalho (Rev Rene)
Objective: to understand the experiences of stigma perceived by mothers of children with congenital Zika virus syndrome and its repercussions. Methods: a qualitative study was carried out with 12 mothers who responded to semi-structured interviews. Correspondence Factor Analysis and Descending Hierarchical Classification were carried out using the IRaMuTeQ software. Results: four classes emerged that deal with the experience of perceiving stigma: Perceiving public discrimination; Stigmatizing behaviors and their repercussions; Feeling guilty and adopting coping strategies; Experiencing rejection from the father, others and feeling lonely. Conclusion: stigma is perceived by mothers of children with congenital Zika virus syndrome in affective, family, and social interactions, expressed through rejection, withdrawal and exclusion resulting in suffering for the mothers, who adopt hiding the child and self-isolation as coping strategies. Contributions to practice: nursing should identify signs of social isolation, deep sadness and stress related to the stigma of being the mother of a child with congenital Zika virus syndrome and draw up care plans to prevent maternal illness.